Representasi Peran Disabilitas Dalam Film Horor Pengabdi Setan 2017 Karya Joko Anwar (Pendekatan Komunikasi Non-Verbal) - Fikri Nugroho Putra Pratama; Muhammad Alfikri (BEST Journal (Biology Education, Sains and Technology), 2022)
This study aims to describe non-verbal communication in representing the role of disability in the Satan's Slave 2017 movie by Joko Anwar. The study uses qualitative method analysis techniques with a descriptive approach. The primary data source in this study is the observation of the Satan's Slaves movie, and the secondary data source is used as a study of the theoretical perspective of journals and books. Data were collected using observation techniques. The results of this study indicate that there is non-verbal communication that represents the role of persons with disabilities in the Satan’s Slaves movie, namely: (1) objects, such as bells and wheelchairs; (2) sign language; (3) paralanguage, like gasping voices; and (4) appearance and behavior. Apart from being an entertainment medium, films can also be informative and educational mediums. The Satan’s Slaves movie becomes a medium for discussion that people with disabilities are humans as usual, so people are avoided from carrying out ableism and disablism, which are only based on stereotypes without an obvious basis. And explain the importance of sign language in interacting with deaf people.